China’s “counterpart assistance” approach to coronavirus: Lessons from the Wenchuan earthquake response - Zhang, Xiaobo; Xu, Lihe (Center for Global Development, 2020)
In early 2020, a new type of coronavirus epidemic (COVID-19) emerged suddenly and spread steadily from China’s Wuhan City, Hubei Province, disrupting China’s social order. The epicenter of the epidemic, Hubei Province lacked medical personnel and epidemic prevention supplies; assistance was urgently needed. This note identifies the Chinese government’s “counterpart aid” strategy in response to the epidemic and explores the strategy’s utility, drawing on earlier experiences with disaster response. Our analysis is based on an earlier research paper examining Wenchuan earthquake relief.